2004
DOI: 10.4049/jimmunol.173.2.1094
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transcription Factor Expression during Discrete Stages of Postnatal Thymocyte Differentiation

Abstract: Postnatal T lymphocyte differentiation in the thymus is a multistage process involving serial waves of lineage specification, proliferative expansion, and survival/cell death decisions. Although these are believed to originate from signals derived from various thymic stromal cells, the ultimate consequence of these signals is to induce the transcriptional changes that are definitive of each step. To help to characterize this process, high density microarrays were used to analyze transcription factor gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 65 publications
10
47
0
Order By: Relevance
“…Microarray studies of the murine thymocyte subsets have been performed by Petrie and coworkers (19). By mining these data for thymic Wnt target genes, we found that p150,95, fos, and jun were expressed at high levels at the DN1 stage and rapidly decreased in the more mature stages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Microarray studies of the murine thymocyte subsets have been performed by Petrie and coworkers (19). By mining these data for thymic Wnt target genes, we found that p150,95, fos, and jun were expressed at high levels at the DN1 stage and rapidly decreased in the more mature stages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is also possible that some additional trans-acting factors are required for TEA activity but are only expressed in DP thymocytes. In this regard, it is notable that the expression of Ets family transcription factors, which are predicted to bind to the TEA promoter, are up-regulated as cells transit from the DN to the DP stage of thymocyte development (24). It is also possible that the TEA promoter has a 5Ј region with insulator activity.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly occurring translocations juxtapose the regulatory regions of TCR genes, located at chromosomes 14q11, 7q32-36, and 7p15, with proto-oncogenes, usually transcription factors, that include Tal1, Tal2, Lyl1, Lom2, and Lck [4]. Intriguingly, some of these transcription factors are expressed in early (DN) thymocytes [39], and the oncogenic fusion transcripts are thought to cause dysregulated growth and maturation arrest of the lymphoblasts. Other chromosomal translocations, not involving the TCR genes, were also reported in T-LBL [40,41].…”
Section: Discussionmentioning
confidence: 99%